Peningkatan Keterampilan Komunikasi Lisan Siswa sebagai Fungsi dari Teknik Instruksi Diri - Ningsih, Diah Ayu Pratiwi; Legowo, Edy; Hidayat, Rian Rokhmad (Jurnal Kajian Bimbingan dan Konseling, 2017)
The purpose of this study was to test the effectiveness of self-instruction techniques to improve student’s oral communication skills in the learning process. This study was an experimental study using a single case experimental with A-B designs. The subject was three students from tenth grade senior high school which had a problem with their oral communication during the learning process. Oral communication skills data were collected using Oral Communication Skills Observational Instruments. Data analysis techniques used were statistical analysis with percentage technique, and split-middle technique also clinical analysis technique which declared by significant other. The results show that after carrying out the self-instruction, subject’s oral communicating skills in the classroom learning process increases.